The Influence of Foreign Direct Investment (FDI), International Tourism and Export Value on Economic Growth in Member Countries of the Organization of Islamic Cooperation (OIC) During 2010-2020 - Imazzuman Siddiqi; Sunaryati (Bulletin of Islamic Economics, 2023)
Studies the effect of FDI, international tourism, export on economic growth have various results. Therefore, this study aims to determine the effect of FDI, international tourism, and exports on economic growth in OIC member countries in the 2010-2020 period using the panel data regression method. The number of samples used in this study were 45 countries. Simultaneously, there is a significant influence between the variables of FDI, international tourism, and export value on economic growth in OIC member countries. While partially FDI shows negative and significant results. On the other hand, international tourism has a positive and significant effect and exports also have a positive and significant effect. This study is only limited to 11 periods and three independent variables. For future researchers, it is expected to develop the number of variables and can increase the observation time.